Shadow AI sebagai sumber risiko operasional dalam industri Perbankan Syariah - Nurahmani, Marsheila Fithri Aisyah (Maliki Interdisciplinary Journal, 2026)
The development of artificial intelligence in the financial sector has opened up many new opportunities, but it has also created new challenges, particularly in the Islamic banking industry. One area that has not yet been extensively studied is the emergence of artificial intelligence systems operating outside of official oversight. These systems are referred to as Shadow AI. This study aims to understand and analyze Shadow AI as a new source of risk in the Islamic banking industry using a systematic literature review approach. This study analyzed 23 articles from various sources, including Scopus, Google Scholar, and accredited national journals published between 2019 and 2026. The results indicate that Shadow AI poses layered risks, including Sharia compliance risks, cyber risks, reputational risks, and conventional operational risks. The study also found that there is currently no comprehensive conceptual framework for integrating Shadow AI into the operational risk management of Islamic banking. This study contributes by offering a risk mapping of Shadow AI and governance recommendations based on the principles of maqashid syariah. Thus, this research can help the Islamic banking industry better understand and manage risks associated with Shadow AI, thereby enhancing security and Sharia compliance in its operations.